The Effectiveness of Role-play Integrated Multisensory Learning to Enhance Students' Confidence and Speaking Skill - Sahlan, Sahlan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Lack of self-confidence and speaking abilities can hinder student learning. Students without self-confidence struggle to express their views and opinions, resulting in poor speaking skills. This study examines whether Role-play Integrated Multisensory Learning (RIML) boosts students' self-confidence and speaking skills. This quantitative experimental study uses an explanatory model and non-equivalent control group design. This study included 30 control and 30 experimental students. Grade 1 elementary school 93 Kendari State Elementary School children were purposively sampled for the study. This study collected data using observation. In this study, students' confidence and speaking skills in five were measured in four ways. This study analyzed data using normality and homogeneity tests. Additionally, SPSS with an independent sample t-test was used to assess the data. Participants' self-confidence and speaking skills improved significantly after the Role-play Integrated Multisensory Learning (RIML) intervention. The experimental group had a high average score of 5,9.0, rising to 91.3 on student confidence and 83.2 on student speaking skills. Additionally, the significance value for each variable is 0.000 <0.05. The findings in this study indicate an improvement in elementary school students' confidence and speaking abilities after receiving an intervention in the form of Role-play Integrated Multisensory Learning (RIML).RIML learning uses all senses in roleplay learning to assist students in understanding the context of learning and practicing speaking skills to gain confidence. Future studies may integrate multisensory features into other learning approaches to stimulate students with varied learning styles.